A CONTRASTIVE ANALYSIS OF SEMANTIC AND PRAGMATIC FEATURES OF THE WORDS DENOTING BIRDS IN ENGLISH AND VIETNAMESE (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Words denoting birds exists in all languages in the world. They take part in all human spectrums and play an important role in the process of communication. Metaphorical meanings of the words denoting birds can create negative or positive perceptions on its audiences. They are typical kinds of words with specific characteristics, which other kinds of words can not have. Especially, they are used to express human’s thoughts, emotion, evaluation, behaviour and attitude, belief, etc. From what noted above, by taking and analysing various samples, this research aims at finding semantic similarities and differences, cases of pragmatics, and cultural characteristics. Obviously, clarifying the semantic and pragmatic features of WDBs in a contrastive analysis view between English and Vietnamese is a very necessary job practically and theoretically. Hopefully, this research is useful to those who are studying English as second language as well as Vietnamese.